Design, Synthesis, and Spectroscopic Elucidation of 3-Methyl-1-Phenylpyrazol-5-One: A Cheminformatics-Aided Approach to Heterocyclic Drug Scaffolds - Abhishek Upadhyay; Sumit Moulekhi; Km. Shilpi Mishra (International Journal of Cheminformatics, 2025)
Pyrazolone, a notable heterocyclic compound, has drawn increasing interest due to its broad pharmacological profile and structural versatility. The synthesis, characterisation, and biological assessment of new pyrazolone derivatives are examined in this work. A comprehensive review of existing synthetic strategies is presented, emphasizing green and efficient methodologies. Novel derivatives were synthesized using varied starting materials and catalytic systems, followed by structural confirmation through spectroscopic analyses, including NMR, IR, and mass spectrometry. The synthesized compounds were evaluated for their biological activity using both in vitro and in vivo assays, revealing promising anti-inflammatory, antimicrobial, and anticancer potential. Mechanistic insights into their biological action were explored at the molecular level, supported by structure-activity relationship (SAR) analysis to identify features contributing to enhanced bioactivity. The results underline pyrazolone’s potential as a scaffold for therapeutic development. In parallel, the thesis addresses the synthesis and mechanistic study of coumarin via the Pechmann condensation reaction. Coumarin was synthesized in high yield (86%) using ethyl acetoacetate and resorcinol under mild acidic conditions, with characterization confirmed by IR, 1H NMR, and 13C NMR spectroscopy. Kinetic studies were conducted across a temperature range of 273–313 K, yielding an apparent activation energy of 34.7 kJ/mol. Complementary DFT calculations (M06-2X) provided mechanistic clarity, outlining a three-step pathway: transesterification, intramolecular hydroxylalkylation, and dehydration. The intrinsic activation energies for these steps were 136.7, 76.5, and 134.0 kJ/mol, respectively, with transesterification identified as the rate-determining step. The theoretical activation energy (40.0 kJ/mol) aligned well with experimental data, validating the proposed mechanism. Together, these investigations contribute valuable insights into heterocyclic compound synthesis and reactivity, with implications for pharmaceutical and industrial applications.
Keywords: Density Functional Theory (DFT); Heterocyclic compounds; Pechmann condensation; Structure-Activity Relationship (SAR); pyrazolone derivatives